2021
DOI: 10.1007/s10661-021-09303-8
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus: occurrence, surveillance, and persistence in wastewater

Abstract: it will help in knowing if there are asymptomatic carriers, as such people do not show any signs of symptoms but shed the viruses in feces. The present review focuses on the epidemiological surveillance of wastewater for coronaviruses, as in recent years these are increasingly causing global pandemics. In this review we have discussed, the four pertinent areas of coronavirus study: (1) occurrence of coronavirus in wastewater, (2) wastewater based epidemiological surveillance of coronaviruses, (3) epidemiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 92 publications
0
3
0
2
Order By: Relevance
“…Could water contamination used in crops be contaminated with SARS-CoV-2 viral particles? SARS-CoV-2 viral RNA has been detected in infected persons' feces, and studies have also reported its occurrence in wastewater and surface water bodies [ 37 , 52 ]. Therefore, water may be a possible route to virus outbreaks.…”
Section: Resultsmentioning
confidence: 99%
“…Could water contamination used in crops be contaminated with SARS-CoV-2 viral particles? SARS-CoV-2 viral RNA has been detected in infected persons' feces, and studies have also reported its occurrence in wastewater and surface water bodies [ 37 , 52 ]. Therefore, water may be a possible route to virus outbreaks.…”
Section: Resultsmentioning
confidence: 99%
“…High sensitivity and a fast turnaround time of SARS-CoV-2 assays are crucial in the early detection of outbreaks in the population and their surrounding environment. Wastewater surveillance is gaining significance in the early detection of outbreaks, offering passive surveillance that has the potential to mitigate population incentives and mobility activities ( 28 30 ). A duplex real-time RT-PCR SARS-CoV-2 assay based on two ultra-conserved SARS-CoV-2 sequences has been reported to detect all variants (including the Omicron variant) in clinical and wastewater samples ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al (2021) sugieren la importancia de la detección del SARS-CoV-2 en aguas residuales para acelerar el diagnóstico masivo de COVID-19 y el desarrollo de medidas de control como la desinfección en plantas de tratamiento de aguas residuales durante pandemias virales. Basavaraju et al (2021) han sugerido un doble propósito para el estudio del coronavirus en aguas residuales, incluyendo la detección temprana de brotes y la estimación de personas infectadas, para mitigar el impacto de esta enfermedad en una comunidad. Coronado et al (2021) detectaron la presencia de SARS-CoV-2 en aguas residuales de la Ciudad de México, mostrando la presencia en 6 muestras del río y cinco muestras de agua de riego, relacionando la mayor concentración viral en muestras con la cercanía a la Ciudad de México.…”
Section: Detección De Sars-cov-2 En Sistema De Drenajeunclassified
“…En este sentido, la vigilancia de las aguas residuales puede aplicarse como una medida de mitigación adecuada y, por lo tanto, no hay excusa para que un brote se convierta en algo más que un brote. Por ejemplo, la epidemiología basada en aguas residuales (WBE, por sus siglas en inglés) es una herramienta especialmente útil para la alerta temprana de brotes de COVID-19 en grandes comunidades, tal como lo demostraron anteriormente Basavaraju et al (2021). Adicionalmente, las personas que viajan en aviones y cruceros pueden ser monitoreadas de manera discreta e indirecta durante el viaje.…”
Section: Introductionunclassified